Association Between Food Choice Motives and Food Consumption in Young Adults: Gender, Obesity and Stress-Related Differences Among University Students - Fatma Ilgaz; Mehmet Fisunoğlu (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: This study was designed to determine the association between food choice motives and consumption of healthy and unhealthy foods in young adults, and to investigate if there is a difference in food choice motives between specific subgroups according to gender, obesity or the presence of depression, anxiety or stress. Material and Methods: The study was planned as a cross-sectional study, and 1000 undergraduate students enrolled in the 2017-2018 academic year were included. Data on students’ food choice preferences and the underlying motivations were collected through face-to-face interviews using the Food Choice Questionnaire (FCQ), while data on symptoms of depression, anxiety, and stress were obtained using the Depression Anxiety and Stress Scale-42 (DASS-42). Food consumption was recorded using a semi-quantitative food frequency questionnaire, and the consumption of dairy products, whole grains, fruits, and vegetables was classified as “healthy”, whereas the consumption of fast food, sugar-added foods, and junk food was evaluated as “unhealthy” food consumption. Mean scores of the importance were calculated for gender, BMI, and DASS-42 subscales. The food choice motives within each category were subsequently ranked from the most to the least important based on these mean scores.Results: There was a significant difference between groups in terms of mean scores for importance of food choice motives, particularly related to gender, depression, and stress status. For food choice, sensory appeal was the most important motive in all groups, followed by ‘price’ or ‘convenience’. Gender and depression-anxiety-stress status were found to be relatively more effective on the rank order of food choice motives compared to BMI. Consumption of healthy foods was positively correlated with ‘health’, ‘natural content’ and ‘weight control’ motives; however, unhealthy food consumption was negatively associated with these factors (p